1997
DOI: 10.1074/jbc.272.29.18125
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Quenching of Phototransduction

Abstract: Quenching of phototransduction in retinal rod cells involves phosphorylation of photoactivated rhodopsin by the enzyme rhodopsin kinase followed by binding of the protein arrestin. Although it has been proposed that the mechanism of arrestin quenching of visual transduction is via steric exclusion of transducin binding to phosphorylated light-activated rhodopsin (P-Rh * ), direct evidence for this mechanism is lacking. In this study, we investigated both the role of rhodopsin phosphorylation in modulating its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
110
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 179 publications
(112 citation statements)
references
References 36 publications
2
110
0
Order By: Relevance
“…We show that NHERF1 forms a ternary complex with ␤-arrestin2 and PTHR, which increases the association kinetics of arrestin to the receptor. (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), abbreviated as PTH (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), was a kind gift from Dr. Thomas Gardella (Massachusetts General Hospital, Boston, MA). Monoclonal HA.11 anti-hemagglutinin (HA) antibody was purchased from Covance, and anti-HA and anti-FLAG affinity-agarose were from Sigma-Aldrich.…”
mentioning
confidence: 99%
“…We show that NHERF1 forms a ternary complex with ␤-arrestin2 and PTHR, which increases the association kinetics of arrestin to the receptor. (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), abbreviated as PTH (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), was a kind gift from Dr. Thomas Gardella (Massachusetts General Hospital, Boston, MA). Monoclonal HA.11 anti-hemagglutinin (HA) antibody was purchased from Covance, and anti-HA and anti-FLAG affinity-agarose were from Sigma-Aldrich.…”
mentioning
confidence: 99%
“…1 shows two examples of how synthetic peptides derived from the arrestin sequence influence the formation of extra MII from prephosphorylated samples. The arrestin peptide comprising residues 11-30 (arrestin- (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)) reduced the amount of extra MII formed in a concentration-dependent manner (Fig. 1A, compare traces b and c); at 1000 M, arrestin-(11-30) abolished extra MII nearly to the control level without arrestin (compare traces c and e).…”
Section: Light-induced Interaction Between Rhodopsin and Arrestin Ismentioning
confidence: 99%
“…Peptide competition has already been applied in previous studies to map regions of interaction in the receptor-arrestin complex. Studies with peptides from the surface-exposed sequences of rhodopsin suggested a role of different loop structures in the interaction (26). Regarding the interactive domains in arrestin, Hargrave and co-workers (27) have employed a library of peptides covering the entire sequence.…”
mentioning
confidence: 99%
“…Phosphorylation is an important chemical modification that allows the activated receptors to be further recognized by proteins from the arrestin family (5). Arrestins stop the signal transduction quickly by directly preventing the G-protein access to the cytoplasmic loops of activated receptors (6). This leads to a diminished cellular responsiveness to a specific stimulus, a phenomenon known as homologous desensitization.…”
mentioning
confidence: 99%
“…Next, visual arrestin binds with high affinity and specificity to light-activated, phosphorylated rhodopsin by a mechanism that is incompletely understood (15,16). Experimental evidence suggests that in addition to phosphate binding residues, arrestin contains elements that enable it to specifically recognize the loops of the photoactivated rhodopsin (17)(18)(19). It has been shown that arrestin is able to recognize the activated, unphosphorylated rhodopsin or a C-terminal truncated form of the activated rhodopsin in the presence of a synthetic fully phosphorylated peptide corresponding to the last 19 amino acids of the C terminus of rhodopsin (20).…”
mentioning
confidence: 99%